Strengthening capacity for research and policymaking - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Reducing hunger and poverty depends on the capacity of researchers and policymakers to understand and use food policy analysis. IFPRI’s approach to capacity strengthening has evolved and expanded to better meet developing country needs through collaborative research, training, and institutional development.